Women and the Female in Neoplatonism - Schultz, Jana; Wilberding, James (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2022)
Sosipatra, Hypatia, Macrina: some of the most famous female philosophers of antiquity were connected to Neoplatonism. But what does it mean to be a woman philosopher in late antiquity? How is the inclusive nature of the Neoplatonic schools connected to their ethical, political, and metaphysical ideas? What role does the religious dimension of late Neoplatonism and the role of women as priestesses play in understanding Neoplatonic women philosophers? This book offers thirteen essays that examine women and the female in Neoplatonism from a variety of perspectives, paying particular attention to the interactions between the metaphysics, psychology, and ethics.